Quantity of Coliform Bacteria as Bioindicator of Water Pollution (Case Study: Several Tributaries in Purwokerto City, Banyumas Regency, Central Java) - Rahayu, Nur Laila; Hendarto, Eko; Sulistiyawati, Indah; Agustiani, Rina Dwi (Universitas Atma Jaya Yogyakarta, 2020)
The city of Purwokerto is crossed by several large rivers, this research examines several tributaries of a large river. Some tributaries that pass through the city of Purwokerto are the Raden River, the Caban River, the Jurig River and the Luhur River. Tributaries have the potential to influence water quality. This study aimed to analyze the quantity of coliform bacteria as an indicator of water pollution in several tributaries in Purwokerto City, Banyumas Regency. Microbiological tests were carried out by calculating the total coliform quantity and fecal coliform using the Most Probable Number (MPN) test. Total coliform and fecal coliform can be used as a reference indicator of water quality in the presence of water pollution. The laboratory test results for the quantity of coliform bacteria showed in several tributaries in Purwokerto City, Banyumas Regency, very high in total coliform or fecal coliform, exceeding the water quality standard.